Facilitator Roles in Parenting Education Programs for Low-Income Families in Jakarta and Pandeglang: [Peran Fasilitator dalam Program Pendidikan Pengasuhan Bagi Keluarga Berpenghasilan Rendah di Jakarta dan Pandeglang] - Arlinkasari, Fitri; Hestyanti, Yohana; Abraham, Natasha; Fitriani, Andi; Henry, Eddy; Herarti, Fitriana (ANIMA Indonesian Psychological Journal, 2024)
This study explores the complexities and diversities of the facilitator roles in parenting education programs. The objective is to evaluate how these responsibilities could potentially deviate or expand beyond standard protocols, ultimately contributing to the improvement of parent or caregiver experiences within these programs. Focusing on low-income families in the Indonesian urban and rural contexts, this study emphasizes the crucial role of effective parenting education in empowering parents or caregivers to nurture their children. Focus Group Discussions (FGDs) and participant observation were used to collect data from both facilitators and parents involved in the program. The aim was to explore the facilitators' role in supporting the education (learning) experience of the participating parents or caregivers. This was analyzed based on the perceptions of both facilitators and parents or caregivers. Thematic analysis revealed the diverse functions of facilitators and their impact on the education (learning) experience. While facilitators typically fulfill conventional roles as managers, moderators, educators, and motivators, they occasionally take on additional roles, acting as resource providers to support parents in their parenting journey better. Two distinct patterns emerged from the study: (1) Parents receive personalized assistance and support when facilitators exceed their designated functions, resulting in increased program engagement; (2) However, this extension of certain key functions of facilitators' roles may inadvertently create challenges in maintaining the program's integrity and unique education (learning) mode, particularly in self-learning contexts. Studi ini mengeksplorasi kompleksitas dan keragaman peran fasilitator dalam program pendidikan pengasuhan. Studi ini bertujuan untuk mengevaluasi bagaimana tanggung jawab ini berpotensi menyimpang atau meluas melampaui protokol standar, yang pada akhirnya berkontribusi terhadap peningkatan pengalaman orang tua atau pengasuh dalam program tersebut. Berfokus pada keluarga berpenghasilan rendah dalam konteks perkotaan dan pedesaan di Indonesia, studi ini menekankan pentingnya peran pendidikan pengasuhan yang efektif dalam memberdayakan orang tua atau pengasuh untuk mengasuh anak mereka. Focus Group Discussion (FGD) dan observasi partisipan digunakan untuk mengumpulkan data, baik dari fasilitator maupun orang tua yang terlibat dalam program. Tujuannya adalah untuk mengeksplorasi peran fasilitator dalam mendukung pengalaman pendidikan (pembelajaran) orang tua atau pengasuh yang berpartisipasi. Hal ini dianalisis berdasarkan persepsi fasilitator dan orang tua atau pengasuh. Analisis tematik mengungkap beragam fungsi fasilitator dan dampaknya terhadap pengalaman pendidikan (pembelajaran). Walaupun fasilitator biasanya menjalankan peran konvensional sebagai manajer, moderator, pendidik, dan motivator, mereka terkadang mengambil peran tambahan, bertindak sebagai penyedia sumber daya untuk mendukung orang tua dalam perjalanan pengasuhan mereka dengan lebih baik. Dua pola berbeda muncul dalam studi ini: (1) Orang tua menerima bantuan dan dukungan yang dipersonalisasi ketika fasilitator melampaui fungsi yang ditentukan, sehingga meningkatkan keterlibatan program; (2) Namun, perluasan fungsi utama tertentu dari peran fasilitator dapat secara tidak sengaja menciptakan tantangan dalam menjaga integritas program dan mode pendidikan (pembelajaran) yang unik, khususnya dalam konteks belajar mandiri.